Impact of nutrient management practices and plant growth regulators on growth, productivity and profitability of wheat (Triticum aestivum) - KUMAR, SUDESH; SHARMA, P K; YADAV, M R; SEXENA, RANI; GUPTA, K C; GARG, N K; YADAV, H L (The Indian Journal of Agricultural Sciences, 2019)
This study was conducted during winter season of 2016-17 and 2017-18 at Rajasthan Agricultural Research Institute, Durgapura, Jaipur to evaluate the effect of nutrient management and growth retardants on wheat (Triticum aestivum L.). Results revealed that the application of 150% RDF+FYM led to higher plant height and dry matter accumulation of wheat at all the growth stages (60 days after sowing (DAS), 90 DAS and at harvest) except at 30 DAS (where it was maximum with 150% RDF). The combined application of Chlormequat Chloride (CCC)+Tebuconazole reduced the plant height of wheat by 4.62, 2.25 and 2.86% (60 DAS), 7.07, 2.24 and 3.05% (90 DAS) and 7.35, 2.76 and 4.11% (at harvest) over water spray, CCC and Tebuconazole alone, respectively. The significantly maximum number of effective tillers (423.42 m-2), spike length (10.66 cm) and test weight (40.32 g) were registered with application of 150% RDF+FYM. The combined spray of CCC+Tebuconazole enhanced the test weight by 7.71%, 2.63 and 2.84% over water spray, CCC and Tebuconazole, respectively. The significantly maximum grain, straw and biomass yield of wheat were recorded with 150% RDF+FYM which were 50.87, 50.31 and 50.56% and 12.26, 15.92% and 14.27% higher over control and 100% RDF, respectively. The grain, straw and biomass yields of wheat due to different growth retardant treatments were found statistically at par. The application of 150% RDF+ FYM increased the gross return by 50.74, 13.10 and 3.83% and mean net returns by 60.56, 12.96 and 3.13% over control, 100% RDF and 150% RDF, respectively. Among growth regulators highest net returns (` 68016) and B:C ratio (1.98) were recorded with combined application of CCC+Tebuconazole. It is concluded that integrated nutrient management using 150% RDF+FYM and combined application of CCC+Tebuconazole can be advocated as sustainable strategy for enhancing productivity and profitability of wheat.